2022
DOI: 10.30574/gscarr.2022.12.1.0188
|View full text |Cite
|
Sign up to set email alerts
|

A critical analysis of the extent to which social determinant of health explains health inequalities regarding maternal mortality in Nigeria

Abstract: This article critically analyzes and quantified the extent to which social determinants of health explains health inequalities regarding maternal mortality in Nigeria. Evidence suggests that maternal mortality is predominant in developing countries. This formed the rationale in using Nigeria as a case study for critical analysis. This study showed the relationship between social status/determinants, health inequalities and maternal mortality outcomes in Nigeria. Using a critical analytical approach, this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 22 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…The situation in South Sudan is similar to that of Chad whereby enabling resources, such as the household wealth index, were significantly associated with non-use of ANC services [31]. For instance, a study found that women from the top two household wealth quintiles had an increased utilization of the recommended number of four or more ANC visits compared to their counterparts from the lowest two quintiles [43]. Also, women of lower socioeconomic status and who specifically cannot afford to pay the transport fare to the health facility did not utilize ANC.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The situation in South Sudan is similar to that of Chad whereby enabling resources, such as the household wealth index, were significantly associated with non-use of ANC services [31]. For instance, a study found that women from the top two household wealth quintiles had an increased utilization of the recommended number of four or more ANC visits compared to their counterparts from the lowest two quintiles [43]. Also, women of lower socioeconomic status and who specifically cannot afford to pay the transport fare to the health facility did not utilize ANC.…”
Section: Resultsmentioning
confidence: 99%
“…Women in polygamous households typically worked in the fields for little pay and received little financial support. Their spouses and other family members did not relieve them of their pregnancy-related domestic duties [43].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations